2013
DOI: 10.1002/pc.22492
|View full text |Cite
|
Sign up to set email alerts
|

The crystallization behaviors of copolymeric flame‐retardant poly(ethylene terephthalate) with organophosphorus

Abstract: The crystallization behaviors of copolymeric flameretardant poly(ethylene terephthalate) (PET) with organophosphorus were studied using differential scanning calorimetry (DSC). The results indicated that the degree of tacticity of molecular chain of PET declined due to the presence of organophosphorus which had an important impact on isothermal and nonisothermal crystallization behaviors apparently. In the process of isothermal crystallization, the more organophosphorus the samples contained, the faster the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The results indicated that the crystalline of PET/PACP composites was strengthened. It was caused by the phenyl group‐containing PACP was a kind of heterogeneous nucleation agent . Meanwhile, a slight decrease of the Tc and △ H C of PET/PACP appeared with the increase of PACP contents, for instance, the Tc of PET/15%PACP decreased from that of PET/5%PACP (200.2°C) to 197.0°C, △ H C from 41.95 J/g to 35.80 J/g as well.…”
Section: Resultsmentioning
confidence: 98%
“…The results indicated that the crystalline of PET/PACP composites was strengthened. It was caused by the phenyl group‐containing PACP was a kind of heterogeneous nucleation agent . Meanwhile, a slight decrease of the Tc and △ H C of PET/PACP appeared with the increase of PACP contents, for instance, the Tc of PET/15%PACP decreased from that of PET/5%PACP (200.2°C) to 197.0°C, △ H C from 41.95 J/g to 35.80 J/g as well.…”
Section: Resultsmentioning
confidence: 98%
“…The results indicated that the crystallinity of PET/HPAIPC composites was strengthened. This was caused by the phenyl group containing HPAIPC acting as a kind of heterogeneous nucleation agent. In addition, the T m of PET/HPAIPC composites slightly increased, in contrast to that of pure PET; the corresponding Δ H m of PET/10%HPAIPC and PET/15%HPAIPC increased by 1.46 J/g and 0.63 J/g, respectively. Therefore, one simple conclusion was summarized: the crystallinity of PET/HPAIPC composites could be promoted by the melt-blending of HPAIPC into PET matrix, which could meet application requirements.…”
Section: Resultsmentioning
confidence: 99%
“…For PET, the values of n were 3.1–3.9, which indicates that the nucleation of pure PET may be homogeneous with three-dimensional growth. While the values of n for the composites were 2.9–3.3, implying that the crystal growth of composites was likely linear growth (two-dimensional and three-dimensional growth) after heterogeneous nucleation [ 25 , 26 , 27 , 28 , 29 , 30 ]. The values of Z c increased with the addition of nucleating agents at the same cooling rate, suggesting a higher crystallization rate was caused compared with PET.…”
Section: Resultsmentioning
confidence: 99%